Model for end-stage liver disease score and hemodynamic instability as a predictor of poor outcome in early transjugular intrahepatic portosystemic shunt treatment for acute variceal hemorrhage. Issue 12 (December 2018) - Hermie, Laurens; Dhondt, Elisabeth; Vanlangenhove, Peter; Hoste, Eric; Geerts, Anja; Defreyne, Luc
Abstract : Objective: To evaluate the outcome of early transjugular portosystemic shunt (TIPS) treatment in patients with a trial-compatible high-risk variceal bleeding and secondly to disclose other predictors of early mortality. Materials and methods: A cohort study was conducted on patients referred for a TIPS procedure with or without combined variceal embolization to control acute esophageal variceal bleeding. A total of 32 patients with Child–Pugh C score less than 14 or Child–Pugh B plus active bleeding at endoscopy, admitted for early-TIPS treatment (<72 h), were included. Results: We noted one (3.7%) failure to control bleeding and no rebleeding during 1-year follow-up. Ten (31.3%) patients died within 6 weeks after TIPS placement. Early mortality was associated with model for end-stage liver disease (MELD) score ( P =0.025), MELD score of at least 19 ( P =0.008) and hemodynamic instability at time of admission ( P =0.001). If hemodynamic instability is associated with a high MELD score, the 6-week mortality peaks at 77.8% ( P =0.000). Conclusion: This study confirms the excellent survival results of early-TIPS treatment for acute variceal bleeding in a selected patient group with a low MELD score. Poor survival in hemodynamically unstable patients with high MELD scores (≥19) contests the guidelines that patients with Child–Pugh class C cirrhosis or Child–Pugh class B with active bleeding on endoscopy should deliberately receive preemptive TIPS treatment after endoscopic haemostasis.